acompañamiento y asistencia de la división jurídica de la cámara de representantes. (2022)
As a student of this valuable institution, the Antonio Nariño University, I am proud to be the first to carry out the internship in the honorable Congress of the Republic, opening the doors to my University institution and making the first agreement so that all my colleagues have access to this wonderful experience. , enter directly to the House of Representatives and its Legal Division located in the administrative building doing my corresponding internship in the contracting area , they gave me a lot of growth as a professional since they helped me expand my knowledge on the issues it covers , as is Public Law and state contracting, this allowing me to learn more in depth how contracting is carried out in the House of Representatives, both on public and private issues and that are of great importance to each of the Colombians.